Effective techniques for changing physical activity and healthy eating intentions and behaviour: A systematic review and meta-analysis - McDermott, Máirtín S.; Oliver, Madalyn; Iverson, Don; Sharma, Rajeev (British journal of health psychology, 2016)
Purpose The primary aim of this study was to review the evidence on the impact of a change in intention on behaviour and to identify (1) behaviour change techniques (BCTs) associated with changes in intention and (2) whether the same BCTs are also associated with changes in behaviour. Methods A systematic review was conducted to identify interventions that produced a significant change in intention and assessed the impact of this change on behaviour at a subsequent time point. Each intervention was coded using a taxonomy of BCTs targeting healthy eating and physical activity. A series of meta‐regression analyses were conducted to identify effective BCTs. Results In total, 25 reports were included. Interventions had a medium‐to‐large effect on intentions (d+ = 0.64) and a small‐to‐medium effect (d+ = 0.41) on behaviour. One BCT, ‘provide information on the consequences of behaviour in general’, was significantly associated with a positive change in intention. One BCT, ‘relapse prevention/coping planning’, was associated with a negative change in intention. No BCTs were found to have significant positive effects on behaviour. However, one BCT, ‘provide feedback on performance’, was found to have a significant negative effect. BCTs aligned with social cognitive theory were found to have significantly greater positive effects on intention (d+ = 0.83 vs. 0.56, p < .05), but not behaviour (d+ = 0.35 vs. 0.23, ns), than those aligned with the theory of planned behaviour. Conclusions Although the included studies support the notion that a change in intention is associated with a change in behaviour, this review failed to produce evidence on how to facilitate behaviour change through a change in intention. Larger meta‐analyses incorporating interventions targeting a broader range of behaviours may be warranted. Statement of contribution What is already known on this subject? Prior research on the causal relationship between intention and behaviour has produced mixed findings. Further experimental research to determine the precise nature of these variables is clearly warranted. However, precise guidance on how to change intention is still lacking. What does this study add? This study aimed to identify behaviour change techniques associated with changes in intention and behaviour. Techniques with positive effects on intention were identified; however, these did not have an impact on behaviour. Larger meta‐analyses incorporating interventions targeting a broader range of behaviours may be warranted.